C-Reactive Protein Suppresses the Th17 Response Indirectly by Attenuating the Antigen Presentation Ability of Monocyte Derived Dendritic Cells in Experimental Autoimmune Encephalomyelitis - Shen, Zhi-Yuan; Zheng, Yi; Pecsok, Maggie K.; Wang, Ke; Li, Wei; Gong, Min-Jie; Wu, Feng; Zhang, Lin (Frontiers in Immunology, 2021)
Experimental autoimmune encephalomyelitis (EAE) is a classical murine model for Multiple Sclerosis (MS), a human autoimmune disease characterized by Th1 and Th17 responses. Numerous studies have reported that C-reactive protein (CRP) mitigates EAE severity, but studies on the relevant pathologic mechanisms are insufficient. Our previous study found that CRP suppresses Th1 response directly by receptor binding on naïve T cells, however, we did not observe the effect on Th17 response at that time, thus it remains unclear whether CRP could regulate Th17 response. In this study, we verified the downregulation of Th17 response by a single-dose CRP injection in MOG-immunized EAE mice in vivo while the direct and indirect effects of CRP on Th17 response were differentiated by comparing its actions on isolated CD4+ T cells and splenocytes in vitro, respectively. Moreover, the composition of immune cells was examined in blood and CNS (Central Nerves System), and a blood (monocytes) to CNS (dendritic cells) infiltration pathway was established in the course of EAE development. The infiltrated monocytes derived DCs (moDCs) were proved to be the only candidate antigen presenting cells to execute CRP’s function. Conversely, the decrease of Th17 responses caused by CRP disappeared in above in vivo and in vitro studies with FcγR2B-/- mice, indicating that FcγR2B expressed on moDCs mediates CRP function. Furthermore, peripheral blood monocytes were isolated and induced to establish moDCs, which were used to demonstrated that the antigen presenting ability of moDCs was attenuated by CRP through FcγR2B, and then NF-κB and ERK signaling pathways were manifested to be involved in this regulation. Ultimately, we perfected and enriched the mechanism studies of CRP in EAE remission, so we are more convinced that CRP plays a key role in protecting against EAE development, which may be a potential therapeutic target for the treatment of MS in human.